Sprachen, Völker und Phantome : Sprach- und Kulturwissenschaftliche Studien Zur Ethnizität. - Mumm, Peter-Arnold. (Münchner Vorlesungen Zu Antiken Welten Series, 2018)
The "Münchner Zentrum für Antike Welten" is a joint research center at the LMU in Munich with a permanent visiting professorship. Each year an internationally renowned scholar of Ancient Studies is invited to hold a lecture series on significant interdisciplinary topics. Furthermore, the MZAW organizes congresses and conferences. The series presents these lectures to an audience interested in the history and culture of the ancient world.